Attention to Emotional Information Is Associated With Cytokine Responses to Psychological Stress - Maydych, Viktoriya; Claus, Maren; Watzl, Carsten; Kleinsorge, Thomas (Frontiers in Neuroscience, 2018)
This study investigated effects of mental stress on salivary cytokine levels and attention to emotional stimuli, as well as associations between stress-induced changes of immune and cognitive parameters. A total of 60 young adults were randomly assigned to either a high-stress or a low-stress group, with high stress being induced by (socially evaluated) Paced Auditory Serial Addition Test (PASAT). Saliva samples were collected before, 5 minutes after, and 45 minutes after completion of the stress task, and were assayed for pro- and anti-inflammatory cytokines. Three distinct types of attention – alerting, orienting, and executive control - were measured by the modified Emotional Attention Network Test Integration (E-ANTI). Both stressors triggered significant increases in IFN-α, IFN-γ, TNF-α, IL-2, IL-5, IL-8, IL-10, IL-12p70, and IL-13 at 45 minutes after stress induction (all p’s <.05). Levels of IL-1β and IL-6 increased only in the high-stress group. Alerting attention was positively associated with more pronounced increases of IL-1β, IFN-α, and TNF-α in both groups. Further, better orienting attention after presentation of negative cues predicted higher increases in IFN-α, TNF-α, IL-2, IL-5, and IL-10 in high-stress group. In contrast, better cognitive control was associated with higher levels of IL-17A in low-stress group. We conclude that attention processes modulate the increases of salivary cytokines after stress exposure, and that these effects depend on stress level, particular attention network, and stimulus valence.